2016
DOI: 10.1002/pbc.26065
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Childhood Infections and Immunizations on Childhood Rhabdomyosarcoma: A Report From the Children's Oncology Group

Abstract: Background Rhabdomyosarcoma (RMS) is a rare, highly malignant tumor arising from primitive mesenchymal cells that differentiate into skeletal muscle. Relatively little is known about RMS susceptibility. Based on growing evidence regarding the role of early immunologic challenges on RMS development, we evaluated the role of infections and immunizations on this clinically significant pediatric malignancy Procedure RMS cases (n=322) were enrolled from the third trial coordinated by the Intergroup Rhabdomyosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Radiation therapy is administered with chemotherapy if there is incomplete resection [17,18]. Adherence to immunization schedule (diphtheria, pertussis, tetanus, measles, mumps, rubella and oral polio vaccine) has been shown to have some protective effect preventing development of RMS [19]. Prenatal exposure to ionizing radiation increases the risk of RMS in offspring [20].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is administered with chemotherapy if there is incomplete resection [17,18]. Adherence to immunization schedule (diphtheria, pertussis, tetanus, measles, mumps, rubella and oral polio vaccine) has been shown to have some protective effect preventing development of RMS [19]. Prenatal exposure to ionizing radiation increases the risk of RMS in offspring [20].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that our result is reliable because it was on the highest category. Maternal education is consider a indicator of social background which can be associated with a variety of health-related factors including risk factors associated with childhood cancer as occupational exposures, dietary patterns, exposure to infectious, immunization, breastfeeding [ 26 28 ]. And it has been reported as a confounding factor [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper has shown that genome-wide association was associated with the numbers of years of schooling completed [ 29 ]. Another item that requires attention is that immunization is correlated with education background and incomplete immunization has already been described associated with embryonal tumors [ 28 ]. Human Development Index (HDI) was similar between the different cities that were included on our study so we believe that migration does not interfere on education background [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors remain largely unstudied; however, the Children’s Oncology Group (COG) recently published that immunizations may decrease the population risk of developing RMS [8].…”
Section: Rhabdomyosarcomamentioning
confidence: 99%